Loss of α2-6 sialylation promotes the transformation of synovial fibroblasts into a pro-inflammatory phenotype in arthritis - Yilin Wang (Nature Portfolio, 2021)
Dysregulation of synovial fibroblasts is thought to be an important step in the pathogenesis of rheumatoid arthritis. Here the authors implicate α2-6 sialylation in this process by studying the glycome of these cells in patients and in a mouse model of inflammatory joint disease.